Eddy current measurements of dielectric coating thickness on a weakly magnetic substrate within the medium frequency range - Volodymyr Ya. Halchenko; Ruslana Trembovetska; Volodymyr Tychkov; Viacheslav Kovtun (PLoS ONE, 2026)
A method is proposed for suppressing uncontrollable noise factors in the form of local variations in the electrophysical properties of the weakly magnetic substrate material of tested objects during eddy current measurements of the thickness of dielectric coatings in the medium frequency range up to 100 kHz. As opposed to methods focused on complicating measuring instruments, in particular the use of multi-frequency techniques, swept-frequencies, resource-intensive numerical techniques for computer-based solution of inverse problems, etc., the new approach to solving this problem involves the use of the Taguchi method for robust parameter design of optimal eddy current probes in terms of improving signal-to-noise ratios, which ultimately ensures minimal variability of the useful signal without actually eliminating uncontrollable interference inherent in the tested objects. This made the medium frequency ECPs competitive for the specified measurements compared to high frequency ones due to the simplification of the hardware part of the gauges, the removal of the problem of equipping them with special sensors, and the reduction of their cost. Because of conducting a variance ANOVA analysis, the statistical influence of the design parameters of thickness gauge probes on the characteristics of the output signal was determined. This enabled the establishment of technical requirements for the accuracy of measuring devices in the manufacturing process, as well as the maintenance of operating parameters, specifically frequency and excitation current, within acceptable limits without significantly compromising the optimal signal-to-noise ratio.